ANALISIS PENERAPAN PERMAINAN ORAY-ORAYAN DALAM MENGEMBANGKAN KEMAMPUAN SOSIAL-EMOSIONAL ANAK USIA 5-6 TAHUN DI RA AL-HIDAYAH BANJARANYAR - Yayu Yulaeha; Mahfiah Mahfiah; Yusanti Yusanti; Herlina Wahyuni (Jurnal Intisabi, 2026)
Early childhood aged 5-6 years have different abilities in interacting. This study aims to determine the implementation of oray-orayan games in developing early childhoods’ social-emotional skill aged 5-6 years in RA Al-Hidayah. This study uses a qualitative research method under a phenomenological approach. The results of the study show that the implementation of oray-orayan games is going well, which can develop early childhoods’ social-emotional aged 5-6 years at RA Al-Hidayah. In addition, there are obstacles in implementing oray-orayan game, in the form of early childhood’s difficulties in following the rules of oray-orayan game. To overcome, the researchers used a simulation technique combined with role-playing strategies and giving feedback in the form of applause and love emoji stickers. In conclusion, oray-orayan game combined with simulation techniques, role-playing, and given feedback in the form of applause and love emoji stickers can develop early childhoods’ social-emotional skill aged 5-6 years at RA Al-Hidayah.